Pharmaceutical care in improving adherence to drug treatment (Research, Society and Development, 2021)
Adherence to drug treatment depends on a set of associated factors, and is characterized as crucial for the proper execution of the treatment. Poor adherence can aggravate health conditions and lead to an increase in mortality. One of the activities that make up pharmaceutical care is the promotion and maintenance of treatment adherence. Therefore, this work aims to highlight the importance of the pharmacist and pharmacist care in the adherence process,. A literature review was carried out, based on a search in the PubMed, Google Scholar and Latin American and Caribbean Literature in Health Sciences databases, with a time frame from 2010 to 2021. After screening and applying the inclusion and exclusion criteria, 16 papers were selected.. From these, it was evidenced that pharmaceutical care was applied to different health conditions, from different types of pharmaceutical interventions. Studies have shown improved adherence to drug treatment when associated with pharmaceutical care, in different health contexts, and from a variety of types of interventions. Therefore, it is possible to conclude that pharmaceutical care is shown as a strategic and extremely important practice to promote medication adherence.